Genome scans for hypertension - Munroe, Patricia (Henry Stewart Talks, 2014)
Hypertension: cause of 4.5% of global disease burden, Causes of hypertension, Complex trait: multiple risk factors, Strategies for finding genes, Candidate gene analysis, Genome-wide scans, Blood pressure traits, Genes with major effects?, Linkage analyses, Monogenic forms of hypertension linkage results, Human chromosomes showing regions of linkage with hypertension, Interpretation, Little consistency between studies, Other methodological approaches are required